2012
DOI: 10.3233/cbm-2012-00276
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and oncostatin M are elevated in liver disease in conjunction with candidate hepatocellular carcinoma biomarker GP73

Abstract: The Golgi phosphoprotein GP73 is elevated in the circulation of individuals with a diagnosis of hepatocellular carcinoma. Its usefulness as a biomarker of HCC is questioned, since it has also been reported to be elevated in the circulation of people with liver cirrhosis. Regulation of GP73 by inflammatory cytokines is therefore of interest. The interleukin-6 (IL-6) family cytokines were tested for effects on GP73 mRNA and/or protein levels in human hepatoblastoma HepG2 cells. Levels of GP73 mRNA and protein we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…In addition, STAT3 is constitutively activated in HCC (23). The serum level of IL-6 was also found to be elevated in HCC, and a higher serum level of IL-6 was associated with HCC progression (37). Here, we found that IL-6 expression is increased and positively correlates to the p-STAT3 level in the serum of HCC patients and in the supernatant of co-cultured PBMCs and Huh7 cells.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, STAT3 is constitutively activated in HCC (23). The serum level of IL-6 was also found to be elevated in HCC, and a higher serum level of IL-6 was associated with HCC progression (37). Here, we found that IL-6 expression is increased and positively correlates to the p-STAT3 level in the serum of HCC patients and in the supernatant of co-cultured PBMCs and Huh7 cells.…”
Section: Discussionsupporting
confidence: 55%
“…GOLM1 encodes a Golgi phosphoprotein, also referred as GP73, which is known to respond to viral infections 19 . This molecule has also been tested as a useful circulating biomarker for several viral and non-viral induced liver diseases 39,40 and the serum GOLM1 levels was shown to correlate with serum IL-6 levels in hepatocellular carcinoma 41 . The trans -regulatory network of GOLM1 that we describe here provides further insights into the understanding of the GOLM1-mediated cytokine regulation, not only in cancer but also for infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we found that AdOSM infection did not induce liver injury; however, OSM was capable of inducing IL-33 in liver endothelial cells. OSM was reported to enhance the antiviral response in the hepatoma cell line in vitro (22), and the level of OSM was raised in patients with hepatic cirrhosis (46) or with hepatocellular carcinoma (23). We also stimulated HMEC-1 by OSM, which increased the expression of IL-33 at 16 h and in a dosedependent manner.…”
Section: Discussionmentioning
confidence: 70%
“…OSM has an important role in various biological processes, including hematopoiesis, chemotaxis, inflammation, embryonic development, cell differentiation, and tissue repair (40). Elevated levels of OSM were observed in liver pathology in association with hepatocellular carcinoma in humans (23). OSM enhanced the antiviral properties of type I interferon in a hepatoma cell line of liver epithelial cells and modulated innate and adaptive immune responses in vitro (22).…”
mentioning
confidence: 99%